Adopción de las Normas Internacionales de Información financiera (NIIF) para el grupo de activos fijos de la empresa Novopan del Ecuador S.A. al 31 de diciembre del 2010 - Aguilar Morejón, Maritza Verónica (2011)
This thesis aims to present the methodology to be used for fixed asset group, the changes that must take place in the balance sheets of the company as well as the impact that would receive it.